2016
DOI: 10.1111/camh.12140
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in Practice: an objective measure of attention, impulsivity and activity reduces time to confirm attention deficit/hyperactivity disorder diagnosis in children – a completed audit cycle

Abstract: Background Diagnosing attention deficit/hyperactivity disorder (ADHD) in children and young people typically relies on clinical observation and subjective parent, teacher and self‐reports. The subjective nature of reports combined with contradictory or missing data can result in diagnostic uncertainty and delay. The aim of this study was to assess whether the addition of an objective test of attention, impulsivity and activity (QbTest) as an adjunct to standard ADHD assessment could accelerate the diagnostic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Current service provision for ADHD in the CYPSE is ad hoc and uncoordinated. There is growing evidence within community settings30 32–34 that QbTest has the potential to significantly improve the current assessment pathway having a direct impact on young people’s health, service delivery and criminal justice outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current service provision for ADHD in the CYPSE is ad hoc and uncoordinated. There is growing evidence within community settings30 32–34 that QbTest has the potential to significantly improve the current assessment pathway having a direct impact on young people’s health, service delivery and criminal justice outcome.…”
Section: Discussionmentioning
confidence: 99%
“…QbTest demonstrates good psychometric properties28 29 and has the additional benefit over other computer tasks of measuring activity level, a core symptom of ADHD 30. There are several studies that demonstrate the clinical utility of QbTest in aiding diagnosis 31 32. A recent randomised controlled trial found clinicians with access to the QbTest report were more likely to reach a diagnostic decision about ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, further evidence is needed to help clinicians and healthcare service managers decide whether adding QbTest to clinical assessment of ADHD is cost effective. A recent audit reported that adding QbTest to ADHD assessment in a child and adolescent service reduced time to diagnosis and resulted in cost savings (Hall et al, 2016). Although these results offer some promise, further research is needed to determine how best to implement the test to enhance diagnostic decision-making in a cost-effective way.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified the potential utility of the QbTest as a clinical tool to aid ADHD assessment and management [16]. The test has been shown to: aid in the differentiation of ADHD from other conditions [17][18][19], increase clinician confidence in diagnostic decision-making [15], reduce the number of appointments to make a diagnosis [15], and result in cost-savings to health services [20].…”
Section: Introductionmentioning
confidence: 99%